Regional oxygen saturation measured by two different oximetry monitors in infants and children undergoing living donor liver transplantation with bilirubin measurements: A prospective observational study. Issue 3 (11th November 2022) - Magasich‐Airola, Natalia Patricia; Momeni, Mona; Sanchez Torres, Cristel; De Magnée, Catherine; Tambucci, Roberto; Reding, Raymond; Pirotte, Thierry
Abstract: Background: Tissue oximetry devices use wavelengths in the 680–870 nm range to separate between oxygenated/deoxygenated hemoglobin. Conjugated bilirubin has an absorption peak at 730 nm. Aims: We hypothesized that ForeSight Elite using 5 wavelengths reduces interference from bilirubin and shows higher regional tissue oxygen saturation (rSO2 ) than INVOS 5100C incorporating 2 wavelengths. Methods: Infants and children undergoing living donor liver transplantation were included between March 2019 and September 2020. Cerebral and somatic rSO2 were measured, and real‐time simultaneous data were collected. Additionally, measurements were collected at (1) baseline, (2) beginning of dissection phase, (3) beginning of anhepatic phase, (4) reperfusion phase, and (5) skin closure. Bilirubin level was available at baseline and at reperfusion. Hyperbilirubinemia was defined as bilirubin level ≥1.0 mg/dl. Results: Thirty‐three patients with median age of 27 months and median weight of 12 kg were included. Baseline bilirubin levels were higher compared to values at reperfusion ( p = .021). A linear mixed effects model considering bilirubin as fixed and patient as random effect showed that there was a statistically significant difference in cerebral rSO2 readings in function of time ( p = .031), device ( p < .001), and bilirubin concentrations ( p = .007) but not for hemoglobin ( p = .347), SpO2 ( p = .882), and arterial partial pressure of CO2 (Pa CO2 ) ( p = .146). The model showed that there was a statistically significant difference in somatic rSO2 readings in function of device ( p < .001) and bilirubin concentrations ( p = .023) but not for time ( p = .074), hemoglobin ( p = .954), SpO2 ( p = .108), and Pa CO2 ( p = .775). Bland–Altman plot analyzing cerebral and somatic rSO2 between both devices showed respectively a mean absolute bias and 95% limits of agreement of 21.73% (−10.21 to 53.67) and 19.52% (−29.51 to 68.54). Conclusions: Oximetry devices emitting light at >2 wavelengths may overcome interference from hyperbilirubinemia providing higher rSO2 readings.